Columbia, Mo. Gen. Ordinances ch. 17, §§ 160-64 (1890) - (:unkn) unknown (My University, 1890)
Chapter XVII: Carrying Concealed Weapons-Firing Guns, Pistols, Fire Crackers, Etc., May 22, 1890: Regulated discharge of firearms or other explosive compounds within Columbia city limits. Also regulated sensitive places while conceal carrying, including: Any church or assemblage of religious worship, any school, any assemblage for educational, literary, or social purpose, or any other public assemblage for any lawful purpose other than military, militia, or law enforcement purposes.
Keywords: DISCHARGE; CARRY - CONCEALED; SENSITIVE PLACES